Analysis of Genetic Engineering Material Misconceptions in Biology Textbooks for Ninth-Grade in Yogyakarta - Silfi Pratiwi; Purwanti Pratiwi Purbosari; Oktira Roka Aji; Rinaldi Rizal Putra (Pascasarjana Universitas Negeri Malang (UM), 2024)
Textbooks play a pivotal role in the pedagogical landscape, serving as indispensable aids for learning, founts of knowledge, and platforms for practical application. This study endeavors to scrutinize the content of textbooks, specifically focusing on ninth-grade biology textbooks within the educational milieu of Yogyakarta City, and to juxtapose these contents with existing literature to discern potential misconceptions. Employing a descriptive qualitative approach, the investigation centers on printed biology textbooks utilized in ninth-grade curricula across junior high schools in Yogyakarta. The selection of textbooks for analysis was based on their prevalence as instructional materials, as determined through survey data. Genetic engineering emerged as the focal point for identifying misconceptions within the chosen textbooks. The tool employed for this purpose was a meticulously crafted misconception analysis sheet, utilized alongside textual scrutiny. Analysis revealed the presence of misconceptions within both Textbooks A and B. Textbook A exhibited one instance of misidentification and one of oversimplification, while Textbook B featured two instances of oversimplification. The prevalence of misconception categories in Textbook A was calculated at 5.88% for misidentification and an equal percentage for oversimplification. In Textbook B, the percentage rose to 15.38%, exclusively attributed to oversimplification. Despite the relatively low incidence of misconceptions in both textbooks, these findings underscore the imperative of mitigating such inaccuracies in future editions.DOI: 10.17977/jps.v12i22024p063